Superdotação e criatividade: análise de dissertações e teses brasileiras - Zavitoski, Pollyana [UNESP] (2015)
A theme currently much discussed in the educational field is special education in a inclusive education approach for students with giftedness. This study aims to broaden the understanding of giftedness, through the literature review and analysis of 12 studies available in the portal of Digital Library of Theses and Dissertations (BDTD) and the Portal Capes with the descriptions: Creativity and giftedness and Creativity and High skills, aiming thereby to analyze the productions previously developed, since creativity is considered not only as an intellectual capacity above average, but also engaging in a task, and both factors may be related to giftedness. Analyzed research by categories defined by th author, and the data tabulated and analyzed descriptively. The study results showed that the first study that linked the above terms was carried out in 2005, with most research focusing on the south of the country and having, mostly teachers as audience. Renzulli stands out as the most widely used theoretical basis. It is considered important the work of the creativity of students with giftedness, as well as the full development of their potential, and invest in training teachers about the theme, aiming to demystify issues related to giftedness